REQUIREMENT OF SUPPLEMENTAL IRRIGATION FOR DRY SEASON COMMON BEAN IN GOIÁS - Heinemann, Alexandre Bryan; Stone, Luís Fernando (IRRIGA, 2015)
REQUIREMENT OF SUPPLEMENTAL IRRIGATION FOR DRY SEASON COMMON BEAN IN GOIÁS ALEXANDRE BRYAN HEINEMANN1 E LUÍS FERNANDO STONE2 1 Embrapa Arroz e Feijão, Santo Antônio de Goiás, GO, alexandre.heinemann@embrapa.br 2 Embrapa Arroz e Feijão, Santo Antônio de Goiás, GO, luis.stone@embrapa.br 1 ABSTRACT Common bean crop is grown in Goiás state in three crop seasons, "wet”, “dry”, and autumn/winter. In "dry" crop season, common bean yield is lower and it can be attributed in large part to the water deficit during its cycle. The use of supplemental irrigation can be an alternative to overcome this stress and increase grain yield. The objective of this study was to quantify the impact of water stress in "dry" season common bean and the irrigation depth required to mitigate this stress, using the CSM-CROPGRO-Dry bean simulation model. The model was calibrated and evaluated against observed data set for Pérola cultivar. Grain yield for six sowing dates (10/1, 20/01, 30/1, 10/2, 20/2, and 28/2) and three soil classes (Oxisol, Ultisol, and Inceptisol) were simulated considering growth under rainfall and growth with supplemental irrigation, using daily climatic data of 26 weather stations in Goiás for the period of 33 years. The relative impact of water deficit, estimated by the grain yield gap in both cases, was 48%. Soil classes had low impact on average values of irrigation depth required as well as on irrigated grain yield. The irrigation depth required increased from 70 to 157 mm and the grain yield decreased from 3,813 to 3,510 kg ha-1 with the advance of sowing date. Keywords: Phaseolus vulgaris, water deficiency, simulation model. HEINEMANN, A.B.; STONE, L.F. REQUERIMENTO DE IRRIGAÇÃO SUPLEMENTAR PARA O FEIJOEIRO DA SAFRA DA SECA EM GOIÁS 2 RESUMO O feijoeiro é cultivado em Goiás em três safras, “águas”, “seca” e outono/inverno. Na safra da “seca”, com semeadura de 01/01 a 28/02, a produtividade do feijoeiro é menor e pode ser atribuída, em grande parte, a ocorrência de deficiência hídrica durante o seu ciclo. O uso de irrigação suplementar pode ser uma alternativa para superar esse estresse e incrementar a produtividade. O objetivo deste trabalho foi quantificar o impacto da deficiência hídrica no feijão da “seca” e a lâmina de irrigação requerida para mitigar essa deficiência, utilizando o modelo de simulação CSM-CROPGRO-Dry bean. O modelo foi calibrado e validado por meio da comparação de dados observados e simulados para a cultivar Pérola. Foram simuladas a produtividade para seis datas de semeadura (10/1, 20/01, 30/1, 10/2, 20/2 e 28/2) e três classes de solo (Latossolo, Cambissolo e Argissolo), considerando o crescimento sob precipitação pluvial ou com o uso da irrigação suplementar, utilizando dados climáticos diários de 26 estações meteorológicas de Goiás para o período de 33 anos. O impacto relativo da deficiência hídrica, estimado pela diferença de produtividade nas duas situações, foi de 48%. As classes de solo tiveram pouco impacto na lâmina media requerida como também na produtividade irrigada. A lâmina média de irrigação requerida aumenta com o avanço da data de semeadura, variando de 70 a 157 mm, e a produtividade decresce de 3.813 a 3.510 kg ha-1. Palavras-chave: Phaseolus vulgaris, deficiência hídrica, modelo de simulação.